Targeting O-Acetyl-GD2 Ganglioside for Cancer Immunotherapy - Julien Fleurence; Sophie Fougeray; Meriem Bahri; Denis Cochonneau; Béatrice Clémenceau; François Paris; Andras Heczey; Stéphane Birklé (Journal of Immunology Research, 2017)
Target selection is a key feature in cancer immunotherapy, a promising field in cancer research. In this respect, gangliosides, a broad family of structurally related glycolipids, were suggested as potential targets for cancer immunotherapy based on their higher abundance in tumors when compared with the matched normal tissues. GD2 is the first ganglioside proven to be an effective target antigen for cancer immunotherapy with the regulatory approval of dinutuximab, a chimeric anti-GD2 therapeutic antibody. Although the therapeutic efficacy of anti-GD2 monoclonal antibodies is well documented, neuropathic pain may limit its application. O-Acetyl-GD2, the O-acetylated-derivative of GD2, has recently received attention as novel antigen to target GD2-positive cancers. The present paper examines the role of O-acetyl-GD2 in tumor biology as well as the available preclinical data of anti-O-acetyl-GD2 monoclonal antibodies. A discussion on the relevance of O-acetyl-GD2 in chimeric antigen receptor T cell therapy development is also included.